Sierra Leone : Power Sector Recovery Strategy, Phase I - World Bank (Washington, DC, 2013)
Power Planning Associates has been appointed by the World Bank to prepare a strategy for the recovery of the National Power Authority (NPA). This Preliminary Report presents the findings of the audit and proposes potential counter measures to improve NPA s technical and financial performance. These counter measures are presented at the end of each section of the report and are summarised below. NPA is locked in a downward spiral of under-performance, wherein generation plant breakdowns and fuel shortages exacerbate cash flow constraints. In addition, poor commercial performance, including high losses and low revenue collection rates, are also at the root of the cash flow problems. This cycle needs to be broken at a number of points, and the following series of counter measures represent the Consultant s initial proposals, in order of priority.